Assessing Emergency Egress on Retail Environments Through Pathfinder Simulation - Charisa Pradiptajati; Noor Cholis Idham; Rania Ababssi (Journal of Engineering, Electrical and Informatics, 2026)
Retail environments with high occupant density often experience crowding, which can compromise safety during emergencies, particularly when spatial layouts create constrained circulation and obstructed exits. This study evaluates the evacuation layout of Superindo Monjali, a supermarket in Yogyakarta, using Pathfinder simulation. The analysis focused on circulation geometry, aisle arrangements, cashier positioning, and exit visibility to assess how spatial configurations influence crowd movement and evacuation efficiency. Simulation results showed that, while total evacuation time (39.3 seconds) met recommended safety standards for single-storey buildings, localized bottlenecks, uneven flow distribution, and underutilization of secondary exits highlighted significant architectural limitations. These findings indicate that operational management alone is insufficient to ensure safe egress; spatial design must support efficient and balanced occupant movement. Based on the results, recommendations include improving exit visibility and accessibility, optimizing aisle and circulation layouts, and enhancing signage and wayfinding. The study demonstrates that architectural layout is a critical determinant of evacuation performance and provides a replicable framework for enhancing emergency preparedness in high-density retail settings.